2020
DOI: 10.2478/hukin-2019-0137
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hormonal Responses to High-Intensity Interval Training in Hyperoxia

Abstract: This study aimed to compare selected hormonal responses to a single session of high intensity interval training performed with an increased fraction of inspired oxygen (hyperoxia) and under normoxic conditions. Twelve recreationally trained men (age 24 ± 3 years) performed two sessions of high intensity interval training on a cycle ergometer, in randomized order with hyperoxia (4 L·min-1 with a flowrate of 94% O2) and normoxia. Each session consisted of 5 intervals of 3 minutes at 85% of the maximal power outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Manfredelli et al found the correlation between increase in prolactin and lactate levels during high-intensity exercise (24). However, prolactin response has been more pronounced during exercise in heat compared to cool conditions (25).…”
Section: Discussionmentioning
confidence: 99%
“…Manfredelli et al found the correlation between increase in prolactin and lactate levels during high-intensity exercise (24). However, prolactin response has been more pronounced during exercise in heat compared to cool conditions (25).…”
Section: Discussionmentioning
confidence: 99%